Effects of aging and maternal protein restriction on the muscle fibers morphology and neuromuscular junctions of rats after nutritional recovery. (April 2015) - Confortim, Heloisa Deola; Jerônimo, Leslie Cazetta; Centenaro, Lígia Aline; Felipe Pinheiro, Patrícia Fernanda; Brancalhão, Rose Meire Costa; Michelin Matheus, Selma Maria; Torrejais, Marcia Miranda
Highlights: Maternal protein restriction was conducted during pregnancy and lactation. Muscle fibers and neuromuscular junctions of offspring at 365 days old were analyzed. Ultrastructure and three types of muscle fibers were altered in restricted animals. Modifications in neuromuscular junctions and collagen were also observed. Maternal protein restriction can affect neuromuscular system development. Abstract: Changes in the nutritional status of mothers may predispose their offspring to neuromuscular disorders in the long term. This study evaluated the effects of maternal protein restriction during pregnancy and lactation on the muscle fibers and neuromuscular junctions (NMJs) of the soleus muscle in the offspring of rats at 365 days of age that had undergone nutritional recovery. Wistar rats were divided into two groups: control (CG) – the offspring of mothers fed a normal protein diet (17%) and restricted (RG) – offspring of mothers fed a low protein diet (6%). After lactation, the male pups received standard chow ad libitum . At 365 days, samples of soleus muscle were collected for muscle fiber analysis (HE staining, NADH-TR reaction and ultrastructure), intramuscular collagen quantification (picrosirius red staining) and NMJs analysis (non-specific esterase technique). The cross-sectional area of type I fibers was reduced by 20% and type IIa fibers by 5% while type IIb fibers increased by 5% in the RG compared to the CG. The percentage of intramuscular collagen was 19% lower in the RG. Disorganization of the myofibrils and Z line was observed, with the presence of clusters of mitochondria in both groups. Regarding the NMJs, in the RG there was a reduction of 10% in the area and 17% in the small diameter and an increase of 7% in the large diameter. The results indicate that the effects of maternal protein restriction on muscle fibers and NMJs seem to be long-lasting and irreversible.